Case Study : Situation of Antibiotic Residues in Fresh Chicken and Chicken products sold in Bangkok - Wongvichayaporn, Chayut; Nongpong, Thanaporn; Chevasuwan, Varunthon; Ritdej, Jirawat; Srinapawong, Chirachaya; Phanpathomkun, Paweerat; Asawakarn, Pabhada; Mungkalarungsi, Sujimon (SciTech Research Journal, 2023)
The main cause of antimicrobial resistance is the misuse and overuse of antimicrobials, such as inappropriate use of antibiotics. Antibiotic resistance poses a threat to health. When getting illness, treatment becomes more difficult that requires more public health resources. In Thailand, there are death from drug-resistant infections 20,000-40,000 people each year. Antibiotics have been used in both humans and in livestock. Antibiotics are used in raising broiler chicken for human food. The inappropriate use of antimicrobials results in residues in the chicken meat that is consumed. Consumers exposed to antibiotic residues from consuming chicken meat may lead to resistance problems. The purpose of this study was to examine the situation of antibiotic residues in chicken meat sold in Bangkok. A total of 48 chicken samples, consisted of 26 fresh chicken meat samples, 6 hygienic chicken meat samples, 5 chicken meatball samples, and 11 chicken sausage samples, were tested for antibiotic residues using the Department of Medical Sciences’ Antibiotic Residue Testing Kit. This test kit is 93% accurate, 78.9% sensitivity, 96.7% specificity. Results: Tetracycline antibiotic residues were detected in 12 samples, representing 25% of all samples; Macrolide, Aminoglycoside, Sulfonamide, 6 samples, representing 12.50% and Penicillin group, 11 samples, representing 22.92% from 26 fresh chicken samples. Tetracycline residues were detected in 7 samples, representing 26.92% of all fresh chicken samples. Macrolide, Aminoglycoside, Sulfonamide were detected in 4 samples, representing 15.38%. Penicillin residues were detected in 7 samples, representing 26.92%. For 6 hygienic chicken samples, none of the 6 antibiotic residues were detected. Of the 5 chicken meatball samples, 2 tetracycline groups were detected, accounting for 40% of all chicken meatball samples. 2 samples were detected Macrolide, Aminoglycoside, Sulfonamide, accounted for 40% and Penicillin 3 samples accounted for 60%. In 11 chicken sausage samples, Tetracycline antibiotics were detected in 3 samples, accounting for 27.27% of chicken sausage samples. All and the Penicillin group, 1 sample, accounted for 9.03% Conclusion: Antibiotic residues were found in fresh chicken meat. and chicken products however, no antibiotic residues were found in fresh hygienic chicken meat.